(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ROA, which stands for return on assets, was the variable that was utilized in order to describe the total financial performance of several institutions. The analysis of sample data for the time period 2008-2014 using the multiple regression technique revealed that, with the exception of the capital adequacy ratio (CAR) variable, all other bank-specific variables (asset quality, management efficiency, earning quality, and liquidity) and the macroeconomic variable GDP had significantly influenced the financial performance of sample banks in India. On the other hand, inflation was statistically insignificant in terms of its effect on return on assets from the perspective of ROI. This conclusion was reached on the basis of the fact that rates of inflation had no impact on ROA. The implications of the study demonstrated that even while private sector banks were able to keep their CAR levels at optimal levels, the other factors that were tied to the management and governance of banks had a significant impact on the financial performance of the banks. One of the conclusions of the investigation was that this was the case. In this day and age of globalization, it is very essential for a nation’s economy to have a strong and well-maintained financial system in order to continue its progress and improvement without interruption